2004
DOI: 10.1089/gte.2004.8.80
|View full text |Cite
|
Sign up to set email alerts
|

Preconceptional Cystic Fibrosis Carrier Screening: Attitudes and Intentions of the Target Population

Abstract: The aim of this study was to assess the attitudes and intentions of individuals planning a pregnancy with regard to preconceptional cystic fibrosis (CF) carrier screening and to determine factors associated with a positive and negative/neutral intention to have the test. A survey, based on a questionnaire, was conducted among a stratified random sample of 303 recently married couples (606 individuals). Of the eligible individuals, 70% (n = 380) participated. Of the respondents, 73% had a positive attitude towa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
1
25
0
1
Order By: Relevance
“…The majority of studies in which attitudes were measured showed that individuals of high school and college age had positive attitudes toward 27,28 However, most studies showed that the majority of those questioned did not want to have screening while at school. 19,24,27 Nonpregnant women and couples planning a pregnancy had positive attitudes, [30][31][32][33][34] with 69-89% believing that CF carrier screening should be routinely offered to all couples planning a pregnancy. 30,[32][33][34] Pregnant women had similar attitudes toward screening.…”
Section: Attitudes Toward Cf Carrier Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies in which attitudes were measured showed that individuals of high school and college age had positive attitudes toward 27,28 However, most studies showed that the majority of those questioned did not want to have screening while at school. 19,24,27 Nonpregnant women and couples planning a pregnancy had positive attitudes, [30][31][32][33][34] with 69-89% believing that CF carrier screening should be routinely offered to all couples planning a pregnancy. 30,[32][33][34] Pregnant women had similar attitudes toward screening.…”
Section: Attitudes Toward Cf Carrier Screeningmentioning
confidence: 99%
“…19,24,27 Nonpregnant women and couples planning a pregnancy had positive attitudes, [30][31][32][33][34] with 69-89% believing that CF carrier screening should be routinely offered to all couples planning a pregnancy. 30,[32][33][34] Pregnant women had similar attitudes toward screening. [35][36][37][38][39] Ninety-eight percent of pregnant women believed that the best time to offer screening is before pregnancy.…”
Section: Attitudes Toward Cf Carrier Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Attitudes about population CF carrier screening Overall, individuals with CF, their parents and other relatives are supportive of population CF carrier screening being made available (Watson et al 1991a;Myers et al 1994;Henneman et al 2001a;Poppelaars et al 2003a;McClaren et al 2008;Maxwell et al 2011) as are many members of the general public in studies in which screening was not offered: in the UK (Watson et al 1991a), Belgium (Decruyenaere et al 1992;Welkenhuysen et al 1996), USA (Botkin and Alemagno 1992;Myers et al 1994), Canada (Melancon and De Braekeleer 1996), the Netherlands (Poppelaars et al 2003a(Poppelaars et al , 2003bPoppelaars et al 2004a) and Australia (McClaren et al 2008). Nevertheless, barriers to implementing screening were often acknowledged, in particular, around the lack of prior awareness of CF and perceptions of relevance for those without a family history.…”
Section: Carrier Screening For Cystic Fibrosismentioning
confidence: 99%
“…Factors affecting the decision to accept or decline carrier screening for CF have recently been reviewed by Chen et al 15 Important acceptance factors included 'higher perceived benefits' (eg, not having an affected child, knowing one's carrier status), 'weaker perceptions of barriers' (eg, social stigma, psychological harm), and 'having fewer or no children'. Acceptance factors reported elsewhere were lower perceived negative consequences of test results, 17 more knowledge, 16,17,19 strong perception of the severity of the disease, 15,20,21 high perceived susceptibility, 15,22,23 and higher socioeconomic status, female gender, and age. 15 Important factors for declining, reported by Chen et al, 15 included perceived barriers to obtain the screening, higher parity, lack of knowledge, and weaker perceptions of benefits.…”
Section: Introductionmentioning
confidence: 95%